IITA offers host community free medical care - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
Earlier this year, IITA commissioned a Primary Health Facility in Idi-ose, Akinyele Local Government, Ibadan, under the leadership of the immediate past Director General, Dr Nteranya Sanginga. The facility has since served the locals with primary health services in collaboration with the Oyo State Ministry of Health. On 3 August, as part of IITA’s community based intervention and social responsibility to its over 50 years host community, IITA organized a community outreach program to offer free medical checks to residents of Akinyele community. Over 150 community residents received free health lectures on how to better take care of themselves and manage their health as they grow old. The primary theme of the session’s lecture was on Blood Pressure and Hypertension awareness. Every resident present received free blood pressure check. Those who had high blood pressure received free medical consultation and preliminary medications to manage their health status and continue to lead a healthy life.